Fostering Children and Adolescents’ Creative Thinking in Education. Theoretical Model of Drama Pedagogy Training - Celume, Macarena-Paz; Besançon, Maud; Zenasni, Franck (Frontiers in Psychology, 2019)
Drama Pedagogy Training (DPT), as other drama-based pedagogies, has been related to several outcomes, including creativity enhancement. This enhancement is commonly proven through the measurement of different creative processes. In our review we systematize characteristics, activities and techniques of DPT that are assumed to be related to creativity in order to have a more comprehensive framework to identify the specific DPT elements that are involved in the enhancement of some of the creative processes of children and adolescents. To this end, we identified five creative processes in experimental studies using DPT: divergent thinking, fantasy and imagination, associative thinking, symbolization, and problem solving.These processes were cross referenced with DPT characteristics, activities, and techniques that were argued to be related to creativity enhancement. Our review will propose a model with two main categories and 6 elements as follows: 1. technical drama phases which emphasizes the role of narrative and embodiment through a) corporal and vocal training and b) main drama techniques (e.g. storytelling and improvisation & role-play), and 2. psycho-pedagogical framework which emphasizes the role of a dialogic space through c) playfulness and a d) collaborative, safe space. We also identified e) feedback as an important element of DPT which belongs to both drama technical phases and psycho-pedagogical framework categories. Along with the model, we explain the creative outcomes associated to each of these elements as a means to attire the attention to drama-based pedagogies for the development of creativity in the educational setting. Keywords: creative processes, drama pedagogy, creativity, drama, education